2023
DOI: 10.3390/biotech12010013
|View full text |Cite
|
Sign up to set email alerts
|

A Synergistic pH-Responsive Serum Albumin-Based Drug Delivery System Loaded with Doxorubicin and Pentacyclic Triterpene Betulinic Acid for Potential Treatment of NSCLC

Abstract: Nanosized drug delivery systems (DDS) have been studied as a novel strategy against cancer due to their potential to simultaneously decrease drug inactivation and systemic toxicity and increase passive and/or active drug accumulation within the tumor(s). Triterpenes are plant-derived compounds with interesting therapeutic properties. Betulinic acid (BeA) is a pentacyclic triterpene that has great cytotoxic activity against different cancer types. Herein, we developed a nanosized protein-based DDS of bovine ser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In summary, BeA emerge as the triterpenes exerting the most widespread influence on several key pathways to induce mitochondrial-based apoptosis with the lowest IC50, a TI > 1 and inhibit the chemoresistance-related genes STAT3 and PDL1. Furthermore, we previously demonstrated that BeA synergizes with doxorubicin to increase the effectivity of this drug in A549 cells [45]. These findings collectively indicate that triterpenes impact different pathways depending on the substituents of their rings.…”
Section: Discussionmentioning
confidence: 57%
“…In summary, BeA emerge as the triterpenes exerting the most widespread influence on several key pathways to induce mitochondrial-based apoptosis with the lowest IC50, a TI > 1 and inhibit the chemoresistance-related genes STAT3 and PDL1. Furthermore, we previously demonstrated that BeA synergizes with doxorubicin to increase the effectivity of this drug in A549 cells [45]. These findings collectively indicate that triterpenes impact different pathways depending on the substituents of their rings.…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand, selectivity of BeA could be increased by its encapsulation into a targeted drug delivery system (DDS). Thus, we previously loaded BeA in a protein-based DDS, demonstrating that BeA was synergized with doxorubicin chemotherapy in A549 cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has also attempted to clarify the mechanism of action of individual derivatives. Understanding the interaction between the active molecular component and the therapeutic target will facilitate the development of more effective therapeutic systems [ 83 , 85 , 92 , 94 , 95 , 148 , 149 ]. Further progress in these fields is expected in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cellular internalization of BSA-(Dox+BA) and the accumulation of the Dox in the nucleus were confirmed. The mechanism of action of BSA-(Dox+BA) relied on S-phase cell cycle arrest, DNA damage, caspase cascade activation, and downregulation of epidermal growth factor receptor (EGFR) expression [ 83 ].…”
Section: Delivery Systemsmentioning
confidence: 99%